2019
DOI: 10.1152/ajprenal.00370.2019
|View full text |Cite
|
Sign up to set email alerts
|

Renal SGLT mRNA expression in human health and disease: a study in two cohorts

Abstract: Pharmacological Na+-glucose linked cotransporter (SGLT)2 inhibition is being examined as a renal protection strategy in nondiabetic chronic kidney disease. We quantified renal SGLT mRNA expression in healthy controls (HC), glomerulonephritis (GN), and diabetic kidney disease (DKD) to identify differences in expression across a spectrum of renal diseases. mRNA expression of SGLT1 and SGLT2 in renal tubules and glomeruli, obtained using microdissection and microarray techniques, was evaluated in two large cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Although patients with autoimmune diseases were excluded from large renal outcome trials, the use of SGLT-2i in antineutrophil cytoplasmic antibody-associated vasculitis (AAV) and systemic lupus erythematodes (SLE) for nephroprotection has increasingly been emphasised 2–4. While SGLT-2 was studied in diabetic nephropathy and IgA nephropathy (IgAN), the presence of SGLT-2 specifically in renal vasculitis and lupus nephritis has not been described yet 5…”
mentioning
confidence: 99%
“…Although patients with autoimmune diseases were excluded from large renal outcome trials, the use of SGLT-2i in antineutrophil cytoplasmic antibody-associated vasculitis (AAV) and systemic lupus erythematodes (SLE) for nephroprotection has increasingly been emphasised 2–4. While SGLT-2 was studied in diabetic nephropathy and IgA nephropathy (IgAN), the presence of SGLT-2 specifically in renal vasculitis and lupus nephritis has not been described yet 5…”
mentioning
confidence: 99%
“…Kidneys of HLD served as the control group. As per published reports, mRNA levels in the ERCB were derived using Affymetrix GeneChip Human Genome U133A 2.0 and U133 Plus 2.0 arrays [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…On one hand, mRNA and protein expressions of SGLT2 increased in kidney biopsy specimen of type 2 diabetics with nephropathy [ 34 ]. On the other hand, it was reported that SGLT2 mRNA expression in PTs was lower in type 2 diabetic patients than nondiabetic control [ 67 , 68 ]. A study using human kidney biopsy tissue of glomerulonephritis (minimal change disease, membranous nephropathy, focal segmental glomerulosclerosis (FSGS), IgA nephropathy) showed that tubular SGLT2 mRNA expression was correlated positively with eGFR and negatively with interstitial fibrosis [ 68 ].…”
Section: Time-course Of Greedy Organs (Hyperfunction To Hypofunction/...mentioning
confidence: 99%
“…On the other hand, it was reported that SGLT2 mRNA expression in PTs was lower in type 2 diabetic patients than nondiabetic control [ 67 , 68 ]. A study using human kidney biopsy tissue of glomerulonephritis (minimal change disease, membranous nephropathy, focal segmental glomerulosclerosis (FSGS), IgA nephropathy) showed that tubular SGLT2 mRNA expression was correlated positively with eGFR and negatively with interstitial fibrosis [ 68 ]. It means that when eGFR is high, SGLT2 is highly expressed and the kidney can become greedy.…”
Section: Time-course Of Greedy Organs (Hyperfunction To Hypofunction/...mentioning
confidence: 99%